(untitled) (Prakriti - The International Multidisciplinary Research Journal, 2024)
This research paper explores the intersection of machine learning, remote sensing, and Geographic Information Systems (GIS) with a focus on state-of-the-art systems, applications, and future developments. Machine learning techniques have made significant progress in recent years, enhancing data analysis, classification, and prediction functions to provide better and more efficient solutions in remote sensing and GIS.